Isolasi dan Uji Potensi Bakteri Pelarut Fosfat dari Rhizosfer Tanaman Kakao (Theobroma cacao) - Sutaryo, Setya Puji Handayani; Achmad Himawan; Kristalisasi, Elizabeth Nanik (AGROISTA : Jurnal Agroteknologi, 2024)
Phosphate solubilizing bacteria are important to caccao plants for phosphor ion release, so that it is not attached by Fe or Al ion, and it use by plants. These research purposes  are to isolation of bacteria that is predicted to have potential as phosphate solubilizing bacteria and it’s identification. Research was conducted at Laboratorium Pusat INSTIPER Yogyakarta in March – May 2023. Research used descriptive method, survey at different caccao orchard, sterilization of research tools and materials, sampling of rhizosphere soil of caccao plants, isolation and bacteria identification. Macroscopy observation results were obtained 4 isolates that were showed transparent zones in Pikovskaya’s media and it’s potential as phosphate solubilizing bacteria. Microscopy observation results were obtained phosphate solubilizing bacteria from every location of sampling that are location 1 at Nglanggeran Kulon hamlet (isolate K1P3U5), location 2 at Gunung Buthak hamlet (isolate K2P2U1) and location 3 at Nglanggeran Wetan hamlet (isolate K3P4U5 and K3P2U2), Nglanggeran Village, Patuk Subdistrict, Gunung Kidul Regency. Phosphate solubilizing bacteria that were obtained are Genus Acetobacter from K1P3U5 and K3P4U5 isolates, and  Escherichia from K2P2U1 isolate. From K3P2U2 isolate was not  identification yet.